2008
DOI: 10.3402/rlt.v16i1.10881
|View full text |Cite
|
Sign up to set email alerts
|

On campus, but out of class: an investigation into students’ experiences of learning technologies in their self-directed study

Abstract: FrancesDeepwell f.deepwell@coventry.ac.uk This paper presents an investigation into how students studying at university engage actively with learning technology in their self-directed study time. The case study surveyed 250 students studying at undergraduate and postgraduate level from a purposive sample of departments within one institution. The study has also conducted focus groups and a number of in-depth follow-up interviews with respondents to the survey. In this article we explore three emerging aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 6 publications
0
17
0
1
Order By: Relevance
“…Instructors' skills and motivation are decisive factors and, as Nichols (2008) points out, even where institutional culture, structure and systems are lacking, the initiative will fall on enthusiasts. Moreover, as Deepwell and Malik (2008) found out, students seem to rely strongly on their instructors' support, including guidance and feedback, and the students in our sample do turn to faculty for help.…”
Section: Discussionmentioning
confidence: 55%
“…Instructors' skills and motivation are decisive factors and, as Nichols (2008) points out, even where institutional culture, structure and systems are lacking, the initiative will fall on enthusiasts. Moreover, as Deepwell and Malik (2008) found out, students seem to rely strongly on their instructors' support, including guidance and feedback, and the students in our sample do turn to faculty for help.…”
Section: Discussionmentioning
confidence: 55%
“…For students to further adopt digital technologies that favour their own learning, they need information about how to use them, even when their degree of digital competence is high (Deepwell & Malik, 2008). As set forth by Lai et al (2012), support, advice and motivation from teachers becomes crucial.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Kopcha (2012), Ertmer et al (2012), Ottenbreit-Leftwich et al (2010) and many others showed the importance role of teachers" inside the classroom in supporting the use of technology and how their behavior can facilitate and support students use of technology as they will be more familiar and capable of using technology. Moreover, Deepwell and Malik (2008) as well as Lai (2015) reported that teachers recommendation and guidance on how to use the resources affects their students' self-directed use of technology while increasing their perceived usefulness of such resources and improving their know-how and experiences of technologies in and out of classrooms.…”
Section: Discussionmentioning
confidence: 99%
“…This means that students" believe that such EC course improved their knowledge, experience and interest while expanding their EC resources and chances to use EC technologies inside and outside the classroom. A number of researchers have revealed the importance of both teachers encouragement and students' confidence and in their study on students" perceived usefulness for using learning such technologies inside and outside the classroom (Deepwell and Malik, 2008;Yousafzai et al, 2007). Ertmer et al (2012), Lai (2015), Katyal and Evers (2004) and many others suggested a positive effect for affection support and computer self-efficacy on technology use and adoption by building up perceived usefulness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation